Studies in Third Millennium Sumerian and Akkadian Onomastics: The Designation and Conception of the Personal God - Di Vito, Robert Anthony (1986)
Ph.D. Dissertation; Directors: W.L.Moran and P. Steinkeller. Order No. DA8704476; DissAbstr 47/11 (May 1987) 4075-Acf. DissAbstr 47/11 (May 1987) 4075-A.